Lanth-c in Obesity - Leupen, Alex (Homœopathic Links, 2014)
Alex Leupen is an experienced teacher on the underlying systems in the plant families and the periodic table of the elements pertaining to homeopathic practice. In this column he shares clinical tips.
Keywords: Obesity; Lanthanides; Lanthanum carbonicum; Teasing